Avaliações em larga escala na alfabetização: contextos no ensino público de um município do Estado do Ceará - Silva, Lucas Melgaço da (2016)
The present study shown the characteristics and the structures of five evaluative systematic monitoring of the teaching-learning processes of imprint national, regional and municipal that evaluate the literacy: National Evaluation of Literacy (NEL), Provinha Brasil, Permanent System of Basic Education Evaluation of Ceará (PSBEEC)-alpha, Provinha do PAIC (Literacy Program at the right age) and Municipal evaluation of the 1st year, developed in a city on the state of Ceará. It will also be observed, its methodological pathways in the production of indicators that lead with efficiency the literacy process of children. It was also observed, its methodological pathways for the production of indicators that lead with efficiency the literacy process of children. whereas all treat of assessments that measure literacy, the search assumes the (in)existence of dialogs that complement the realization of its proposals. From the mentioned, this work had as objectives to write the general structure and specific to each evaluation on a large scale in the area of literacy; to make comparative study of evaluations on a large scale in the area of literacy; to confront the results of evaluations on a large scale in the area of adult literacy a city on the state of Ceará. The research methodology is qualitative, in the form of case study, with a descriptive feature. The main results, referring to the object of this study, we identified structural failures with respect to the return of the results to the society; it was observed similar frameworks that occurred between the administrative instances of each evaluation; and that both are linked to specific support programs for literacy and the training of teachers.